Ecotourism as a form of sustainable development - E. V. Shestakova; A. M. Sitzhanova; R. M. Prytkov (Вестник университета)
The article discusses the specificity and current trends of ecological tourism in the context of sustainable development. The authors performed a literary review of the concept of “sustainable development”, grouped the views of various authors on the definition of this concept. The modern normative-legal base of the Russian Federation in the field of steady development is analysed, the list of operating statutory acts in this sphere is revealed. The world practice of tourism development has been studied. The basic principles regulating natural ecological tourism are revealed, plans of strategic development at various levels of management are studied. The authors concluded that the current high tourism potential of the Russian Federation is underused. Ecological tourism can become one of the effective means of nature protection and formation of ecological culture.